FACTORS OF PREDICTION OF FAMILY CRISIS DEVELOPMENT - Falyova, Olena (PSYCHOLOGICAL JOURNAL, 2016)
The paper analyses significant factors connections, determines factors and criteria of prediction of family crisis development (personal growth and destructive reaction of personality) and growth of personal self-realization of woman at the circumstances of family crisis in total number of 648 persons under the study — women and men of 29–56 years old. The sampling population includes married couples (crisis families) — 224 women and 194 men, 104 divorced women and 126 women from common families. The study outcome analysis showed that personal growth of women in crisis conditions is facilitated by: high level of ability to live in the present, see their life as coherent, have independent values and behavior, value their achievements, perceive themselves as they are, realize their feelings, perceive their own aggression, maintain contacts and capacity for creativity; internal locus of control, feeling of personal effectiveness and competency; attention to personal sexuality and initials signs of sexual neuroticism; high level of understanding, emotional attraction, authoritativeness and marriage satisfaction; factor of a full complex of psychological defense; readiness for flexible selection of behavior strategy in conflict situations; sensitivity as understanding of personal needs and feelings. Psychic disadaptation and destructive reaction are caused by: low level of ability to live in the present, see their life as coherent, have independent values and behavior, value their achievements, perceive themselves as they are, realize their feelings, perceive their own aggression, maintain contacts and capacity for creativity; external locus of control; insufficient understanding of personal sexuality, absence of attention to it and high level of sexual neuroticism; low level of understanding, emotional attraction, authoritativeness and marriage satisfaction; choice of competition, adaptability, avoidance of leading behavior strategies in conflict situations; absence of understanding and ability to reflect personal needs and feelings.